Physiological and Molecular Responses in the Gill of the Swimming Crab Portunus trituberculatus During Long-Term Ammonia Stress - Zhang, Jingyan; Zhang, Mengqian; Jayasundara, Nishad; Ren, Xianyun; Gao, Baoquan; Liu, Ping; Li, Jian; Meng, Xianliang (Frontiers in Marine Science, 2021)
Ammonia is a common environmental stressor encountered during aquaculture, and is a significant concern due to its adverse biological effects on vertebrate and invertebrate including crustaceans. However, little information is available on physiological and molecular responses in crustaceans under long-term ammonia exposure, which often occurs in aquaculture practices. Here, we investigated temporal physiological and molecular responses in the gills, the main ammonia excretion organ, of the swimming crab Portunus trituberculatus following long-term (4 weeks) exposure to three different ammonia nitrogen concentrations (2, 4, and 8 mg l–1), in comparison to seawater (ammonia nitrogen below 0.03 mg l–1). The results revealed that after ammonia stress, the ammonia excretion and detoxification pathways were initially up-regulated. These processes appear compromised as the exposure duration extended, leading to accumulation of hemolymph ammonia, which coincided with the reduction of adenosine 5′-triphosphate (ATP) and adenylate energy charge (AEC). Considering that ammonia excretion and detoxification are highly energy-consuming, the depression of these pathways are, at least partly, associated with disruption of energy homeostasis in gills after prolonged ammonia exposure. Furthermore, our results indicated that long-term ammonia exposure can impair the antioxidant defense and result in increased lipid peroxidation, as well as induce endoplasmic reticulum stress, which in turn lead to apoptosis through p53-bax pathway in gills of the swimming crab. The findings of the present study further our understanding of adverse effects and underlying mechanisms of long-term ammonia in decapods, and provide valuable information for aquaculture management of P. trituberculatus.